Urinary incontinence, UTI and its associated health problems among female athletes- an interventional approach - Sobana, R. M.; Jishnu Deva, B. (International Journal Of Community Medicine And Public Health, 2025)
Background: Research over recent decades has shown that lower urinary tract dysfunction such as urinary incontinence (UI) and UTI is common among physically active women, including those in high-impact sports. It is essential to study the rate of prevalence and risk factors in order to prevent and treat the problem among female athletes. Methods: This cross-sectional study assessed the prevalence of UI, UTI, and the effect of an intervention on 138 female athletes aged 17-23 using a self developed questionnaire and follow-up intervention program. Results: UI was reported by 29%, UTI by 48.6%, and both by 35%. Intervention significantly improved awareness and practices. Conclusions: Increased awareness and education can help female athletes overcome UI/UTI-related limitations in performance and quality of life.